Complete sequence of Erwinia piriflorinigrans plasmids pEPIR37 and pEPIR5 and role of pEPIR37 in pathogen virulence - Barbé, Silvia; Llop, Pablo; Blom, Jan van der; Cabrefiga, Jordi; Goesmann, Alexander; Duffy, Brion; Montesinos, Emilio; Smits, Theo H. M.; López, María M. (2017)
Erwinia piriflorinigrans is a newly described pathogen causing necrosis of pear blossoms. Complete sequencing of the 37-kb plasmid pEPIR37 common to 27 E.piriflorinigrans strains revealed homology to sequences of the ubiquitous plasmids pEA29 of the fire blight pathogen E.amylovora, plasmid pEP36 of E.pyrifoliae, plasmid pEJ30 of Erwinia sp. from Japan, and genomic regions of the related Rosaceae epiphytic Erwinia species E.tasmaniensis and E.billingiae. A second 5.5-kb cryptic plasmid pEPIR5, found in 12 E.piriflorinigrans strains, was also sequenced revealing mobilization and replication proteins with similarities to many small ColE1-type plasmids in Erwinia spp. and other enterobacteria. Functional analyses of pEPIR37 introduced into a strain of E.amylovora cured of pEA29 plasmid, which has a reduced virulence, showed a role in increasing symptom development similar to that observed in E.amylovora carrying plasmid pEA29.